The “Complex Dynamic Model of Autonomy Development” in Action: A Longitudinal Multiple Case Study on Language Learners’ Trajectories - Larissa Borges (Studies in Self-Access Learning Journal)
This paper explores the autonomy development in the language learning trajectories of two English major students within the complexity paradigm (Larsen-Freeman, 1997, 2017; Larsen-Freeman & Cameron, 2008). Autonomy is viewed as a complex, evolving phenomenon shaped by life experiences, including setbacks, stability, and progress. The Complex Dynamic Model of Autonomy Development (Borges, 2022) guided this four-year longitudinal study conducted at a university in Northern Brazil. This multiple case study utilized learning narratives, diaries, and a final interview to generate data. Learning narratives depicted the participants’ profile and their learning initial conditions, while diaries captured their reflections on language learning and autonomy. An interview was conducted in the final semester to shed light on how autonomy influenced students’ empowerment and participation in the academic and professional community (Borges, 2019; Murray, 2017; Nicolaides, 2017; Oxford, 2003). The results show that the personalized and complex nature of autonomy development is manifested differently for each student in varying contexts over time. Subsystems like motivation, beliefs, identities, and emotions were found to either enhance or inhibit autonomy along their language learning journeys.